A Brighton Collaboration standardized template with key considerations for a benefit/risk assessment for the Medigen COVID-19 protein vaccine. Issue 15 (6th April 2023) - Estephan, Lila; Liu, Luke Tzu-Chi; Lien, Chia En; Smith, Emily R.; Gurwith, Marc; Chen, Robert T.; ,
Abstract: The Brighton Collaboration Benefit-Risk Assessment of VAccines by TechnolOgy (BRAVATO) Working Group has prepared standardized templates to describe the key considerations for the benefit-risk assessment of several vaccine platform technologies, including protein subunit vaccines. This article uses the BRAVATO template to review the features of the MVC-COV1901 vaccine, a recombinant protein subunit vaccine based on the stabilized pre-fusion SARS-CoV-2 spike protein S-2P, adjuvanted with CpG 1018 and aluminum hydroxide, manufactured by Medigen Vaccine Biologics Corporation in Taiwan. MVC-COV1901 vaccine is indicated for active immunization to prevent COVID-19 caused by SARS-CoV-2 in individuals 12 years of age and older. The template offers details on basic vaccine information, target pathogen and population, characteristics of antigen and adjuvant, preclinical data, human safety and efficacy data, and overall benefit-risk assessment. The clinical development program began in September 2020 and based on demonstration of favorable safety and immunogenicity profiles in 11 clinical trials in over 5, 000 participants, it has been approved for emergency use based on immunobridging results for adults in Taiwan, Estwatini, Somaliland, and Paraguay. The main clinical trials include placebo-controlled phase 2 studies in healthy adults (CT-COV-21), adolescents (CT-COV-22), and elderly population (CT-COV-23) as well as 3 immunobridging phase 3 trials (CT-COV-31, CT-COV-32, and CT-COV-34) in which MVC-COV1901 was compared to AZD1222. There are also clinical trials studying MVC-COV1901 as homologous and heterologous boosters (CT-COV-24 and CT-COV-25). The totality of evidence based on ∼3 million vaccinees to date includes a mostly clean safety profile, with adverse events mostly being mild and self-limiting in both clinical development and post-marketing experience, proven immunogenic response, and real-world effectiveness data. The immunogenic profile demonstrates that MVC-COV1901 induces high levels of neutralizing and binding antibodies against SARS-CoV-2. There is a dose-dependent response and a significant correlation between binding and neutralizing antibody activity. Antigen-specific T-cell responses, particularly a Th1-biased immune response characterized by high levels of interferon gamma and IL-2 cytokines, have also been observed. Coupled with this, MVC-COV1901 has favorable thermostability and better safety profiles when compared to other authorized vaccines from different platforms, which make it potentially a good candidate for vaccine supply chains in global markets.